Thermodynamic Analysis of a Conceptual Fixed-Bed Solar Thermochemical Cavity Receiver–Reactor Array for Water Splitting Via Ceria Redox Cycling - Yang, Song; Li, Lifeng; Wang, Bo; Li, Sha; Wang, Jun; Lund, Peter; Lipiński, Wojciech (Frontiers in Energy Research, 2021)
See the uploaded manuscript. file.